Systemic Transformation, Trade and Economic Growth Developments, Theoretical Analysis and Empirical Results - Westernhagen, Natalja von (Contributions to Economics, 2002)
Since the late 1980s and the beginning of the 1990s, the Commonwealth of Independent States (CIS) and Central and Eastern European Countries (CEECs) have been involved in the transition process. This book compares the progress of some of these economies in transition and analyses their growth potential. The focus lies on the special role that foreign trade liberalisation and foreign direct investment plays in economic growth. Since foreign trade and foreign direct investment are important channels of technology transfer they can substantially contribute to a higher level of economic growth. Based on the gravity model this book investigates potential in foreign trade and foreign direct investment for selected CIS and CEECs with developed OECD economies. Policy options for some of these countries are discussed including issues of foreign trade, foreign direct investment, structural adjustment, and economic growth